Logistics strategy and performance: the case of furniture manufacturing companies in Villa El Salvador, Peru - Davila-Cajahuanca, David (2023)
Objective. To identify whether logistics strategies influence the performance of furniture manufacturing companies in Villa El Salvador. Methods. The study was developed under a quantitative approach, at an explanatory level. Information was collected on logistics strategies with a Likert-type survey in 2018: postponement, internal logistics integration, external logistics integration and proactive logistics, and on logistics performance: lead time, logistics cost, stock-out and customer satisfaction. Econometric methods were used to test the hypotheses. Results. Postponement reduces lead time and logistics cost, but does not influence stock-out or customer satisfaction. Internal logistics integration decreases lead time, logistics cost and stock-out and increases customer satisfaction. External logistics integration decreases lead time, logistics cost and stock-out and improves customer satisfaction. Proactive logistics does not influence lead time, decreases logistics cost and stock-out, and increases customer satisfaction. Conclusion. Logistics strategy influences the performance of companies. This effect could be explained not so much by the structured application of logistics strategies, but because the survey included elements of logistics strategies and because these companies, being members of a cluster, cooperate and coordinate.